2009
DOI: 10.3802/jgo.2009.20.4.203
|View full text |Cite
|
Sign up to set email alerts
|

Major clinical research advances in gynecologic cancer 2009

Abstract: In this review, we summarized nine major clinical advances in gynecology which occurred in 2009. For cervical cancer, the role of human papillomavirus (HPV) test as a screening test, the efficacy of HPV vaccine for middle-aged women, randomized controlled trial (RCT) regarding concurrent chemoradiation using gemcitabine plus cisplatin, and the efficacy of pazopanib for metastatic or recurrent disease were chosen. For endometrial cancer, the necessity of systematic pelvic lymphadenectomy in early endometrial ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…1,2 The risk factors for endometrial cancer include obesity, diabetes, late menopause, unopposed estrogen therapy, and nulliparity. 3 Inherited factors have also been suggested as important risk factors for endometrial cancer.…”
mentioning
confidence: 99%
“…1,2 The risk factors for endometrial cancer include obesity, diabetes, late menopause, unopposed estrogen therapy, and nulliparity. 3 Inherited factors have also been suggested as important risk factors for endometrial cancer.…”
mentioning
confidence: 99%
“…In the current study, we showed our experience for comparing survival and toxicity between TC and AP for CCR in patients with intermediate‐ or high‐risk endometrioid endometrial cancer. We enrolled only patients with endometrioid endometrial cancer because there were very few patients with other histological types who received CCR using TC or AP in our institute, and endometrioid adenocarcinoma is the most common endometrial cancer 2–4 . We found that TC had comparable efficacy for survival to AP for CCR with lesser hematological and non‐hematological, especially, gastrointestinal, toxicities in patients with intermediate‐ or high‐risk endometrioid endometrial cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Endometrial cancer is the most common gynecologic malignancy in the USA, and its incidence has increased to approximately 16% of gynecologic cancers in Korea 1 . More than 80% of patients have International Federation of Gynecology and Obstetrics (FIGO) stages I (64%) or II (20%) of the disease 2,3 . Although most patients with low‐risk endometrial cancer may be cured after surgery, those with intermediate‐ or high‐risk endometrial cancer often show loco‐regional or distant recurrence 4 .…”
Section: Introductionmentioning
confidence: 99%
“…After the promising report of primary analysis [36], long-term follow-up results on PFS and OS were released in 3 years. A total of 631 patients were randomly assigned to receive c-TC (paclitaxel 180 mg/m 2 and carboplatin AUC 6 on D1) or dd-TC (paclitaxel 80 mg/m 2 on D1, 8, 15 and carboplatin AUC 6 on D1) for six cycles every 3 weeks.…”
Section: The Best Possible Treatment Regimens In Ovarian Cancermentioning
confidence: 99%